2022
DOI: 10.1111/fcp.12754
|View full text |Cite
|
Sign up to set email alerts
|

Risperidone in analgesia induced by paracetamol and meloxicam in experimental pain

Abstract: Nonsteroidal anti-inflammatory drugs (NSAIDs) are among the best therapeutic options to treat pain. Their use in combination with other drugs may broaden their applicability in analgesia if their ceiling and adverse effects are reduced. The aim of this study was to evaluate the pharmacological interaction of two NSAIDs, paracetamol and meloxicam, with the antipsychotic drug risperidone in mice, in several experimental tests of nociceptive and inflammatory pain. Antinociception was assessed by dose-response cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The authors showed that this action is mediated by an increase in the activity of both cyclooxygenase 1 (COX-1) and cyclooxygenase 2 (COX-2) which are major targets of non-steroidal anti-inflammatory drugs (NSAIDs). 90,91 In addition, CBD is an inhibitor of lipoxygenase (LOX), which is potentially involved in the production of inflammatory factors.. 92 The antiinflammatory effects of CBD have been repeatedly confirmed in preclinical observations. [93][94][95][96][97] An inhibitory effect on the cytochrome P450 superfamily (CYPs) constituting major enzymes involved in many drug metabolisms, including NSAIDs commonly used in pain management, has also been described.…”
Section: Ionic Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors showed that this action is mediated by an increase in the activity of both cyclooxygenase 1 (COX-1) and cyclooxygenase 2 (COX-2) which are major targets of non-steroidal anti-inflammatory drugs (NSAIDs). 90,91 In addition, CBD is an inhibitor of lipoxygenase (LOX), which is potentially involved in the production of inflammatory factors.. 92 The antiinflammatory effects of CBD have been repeatedly confirmed in preclinical observations. [93][94][95][96][97] An inhibitory effect on the cytochrome P450 superfamily (CYPs) constituting major enzymes involved in many drug metabolisms, including NSAIDs commonly used in pain management, has also been described.…”
Section: Ionic Channelsmentioning
confidence: 99%
“…Observations by Wheal et al conducted on a rat model sought a mechanism for the anti‐inflammatory and analgesic properties of CBD in preclinical models of diabetes. The authors showed that this action is mediated by an increase in the activity of both cyclooxygenase 1 (COX‐1) and cyclooxygenase 2 (COX‐2) which are major targets of non‐steroidal anti‐inflammatory drugs (NSAIDs) 90,91 . In addition, CBD is an inhibitor of lipoxygenase (LOX), which is potentially involved in the production of inflammatory factors.…”
Section: Mechanisms Of Analgesic Actionmentioning
confidence: 99%
“…administration of 1,0 mg/kg of naltrexone (NTX), or naltrindole (NTI) or norbinaltorphimine (nor-BNI), or 5 mg/kg of L-NAME, 0,5 mg/kg of risperidone (RISPER) or tropisetron (TROPI) in the WT assay, using at least 6-8 animals for each of at least 4 doses. The doses used were selected according to previously published studies [8,9] and adjusted according to preliminary experiments.…”
Section: Experimental Designmentioning
confidence: 99%
“…One of the most used is the acetic acid writhing test, which is a tonic visceral pain that mimics a type of human pain and uses a chemical stimulus, a dilution of acetic acid, to induce a characteristic behavior of pain. In this test, the chemical s t i m u l u s induces a wave of contraction of the abdominal muscle followed by extension of the hindlimbs (writhes) and reduction in motor activity [8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the curve was fitted by the computer-derived SAS NLIN Processes (SAS Institute Inc., Carey, NC) to derive the ED 50. [25,26] The ED 25 , ED 75 , and ED 95 were obtained by using the same method (SAS NLIN Processes) [27,28].…”
Section: Neurobehavioral Assessmentsmentioning
confidence: 99%